Unilateral Ovarian Abscess Caused by Salmonella. Issue 4 (2003) - Tohya, Toshimitsu; Yoshimura, Toshihiro; Onoda, Chikashi
Abstract : Background: Patients with unilateral ovarian abscesses due to Salmonella are rare. Case report: A 48-year-old woman with a left ovarian abscess caused by Salmonella group O7 is reported. Conclusion: In our patient, the ovary may have been seeded hematogenously by salmonellae and may have evolved into a local infection.